2009
DOI: 10.1037/a0013773
|View full text |Cite
|
Sign up to set email alerts
|

Information sharing and team performance: A meta-analysis.

Abstract: Information sharing is a central process through which team members collectively utilize their available informational resources. The authors used meta-analysis to synthesize extant research on team information sharing. Meta-analytic results from 72 independent studies (total groups ϭ 4,795; total N ϭ 17,279) demonstrate the importance of information sharing to team performance, cohesion, decision satisfaction, and knowledge integration. Although moderators were identified, information sharing positively predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
546
1
12

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 984 publications
(576 citation statements)
references
References 87 publications
17
546
1
12
Order By: Relevance
“…The model is so reasonable that it surely must be correct-if only we could come up with the proper way of selecting, measuring, and analyzing group interaction. And, in fact, there have been a sufficient number of encouraging findings recently to provide reason for hope that eventually we may be able to document the mediating role of group interaction process, at least in some circumstances (see, Littlepage, Schmidt, Whisler, & Frost,1995;Mesmer-Magnus & DeChurch, 2009). …”
Section: Mediatorsmentioning
confidence: 99%
“…The model is so reasonable that it surely must be correct-if only we could come up with the proper way of selecting, measuring, and analyzing group interaction. And, in fact, there have been a sufficient number of encouraging findings recently to provide reason for hope that eventually we may be able to document the mediating role of group interaction process, at least in some circumstances (see, Littlepage, Schmidt, Whisler, & Frost,1995;Mesmer-Magnus & DeChurch, 2009). …”
Section: Mediatorsmentioning
confidence: 99%
“…However, teams cannot "constantly communicate" and still perform effectively. A meta-analyses examining the relationship between information sharing and team performance found that information sharing was more positively related to team performance when the information shared was unique and related directly to performance outcomes [47], which suggests that time spent sharing redundant or nonrelevant information is not helpful to teams.…”
Section: Synopses and Guidelinesmentioning
confidence: 99%
“…Many studies have shown that teams perform suboptimally because they spend more time discussing shared information than unshared information. In so doing, teams are not employing the informational advantage they should have over individuals (for a recent meta-analysis, see Mesmer-Magnus & DeChurch, 2009). …”
Section: Information Sharing and Team Virtualitymentioning
confidence: 99%